In situ studies of the molecular packing dynamics of bulk-heterojunction solar cells induced by the processing additive 1-chloronaphthalene1. Issue 15 (21st April 2015) - Kwon, Sooncheol; Park, Jin Kuen; Kim, Jehan; Kim, Geunjin; Yu, Kilho; Lee, Jinho; Jo, Yong-Ryun; Kim, Bong-Joong; Kang, Hongkyu; Kim, Junghwan; Kim, Heejoo; Lee, Kwanghee
<x xml:space="preserve">Abstract</x> In situ GIWAXS was used to monitor the molecular packing dynamics and phase separation of bulk-heterojunction composites with a processing additive 1-chloronaphthalene.